Inhibition of HPSE/SDC-2 axis-induced epithelial-mesenchymal transition for treating IC/BPS - Zhengsen Chen; Yuting He; Junjie Zhang; Qingyu Ge; Tianpeng Du; Zongyao Fan; Junyl Zhou; Xin Yang; Baixin Shen; Zhongqing Wei (PLoS ONE, 2025)
Interstitial cystitis/bladder pain syndrome (IC/BPS) plagues patients and clinicians with its unclear etiology and pathogenesis, and ineffective treatments. Destruction of epithelial tissue and proliferation of interstitial tissue are typical pathological features of IC/BPS, in which epithelial-mesenchymal transition (EMT) may play an important role. Both the increased urination frequency observed in mice with acute cystitis induced by cyclophosphamide (CYP) and the disruption of the anti-leakage barrier in urothelial cells induced by LPS are associated with the occurrence of EMT. The expression of heparanase 1 (HPSE) and syndecan-2 (SDC-2) is up-regulated in the bladder mucosa of patients with IC, and both of them can promote the development of EMT. Improvement of lower urinary tract symptoms and restoration of the uroepithelial cell anti-leakage barrier in mice with CYP-induced cystitis after treatment with the HPSE inhibitor OGT2115 and inhibited the development of EMT. We then verified that HPSE binds to SDC-2 and that SDC-2 is a key intermediate protein in the pro-EMT role of HPSE, and that EMT was inhibited by knockdown of SDC-2. SDC-2 exerts its biological function by inhibiting the ubiquitinated degradation of TGF-βR1. Here we identified a novel mechanism by which the HPSE/ SDC-2 axis promotes EMT development and thus causes epithelial dysfunction and altered voiding behavior, providing a new direction for the treatment of IC/BPS.